(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Coronary heart disease and oncological diseases occupy leading positions in the cause of mortality worldwide. The combination of coronary heart disease (CHD) and oncopathology, given the prevalence of both nosologies, is not uncommon. The presence of concomitant CHD in patients with malignant neoplasms in most cases serves as an aggravating factor complicating and / or limiting the treatment of oncopathology. Coronary heart disease in patients with oncopathology can increase the frequency of postoperative complications, hospital mortality, and reduce long-term survival after radical surgery for malignant neoplasm. Myocardial revascularization, performed as the first stage in patients with hemodynamically significant stenosis of the coronary arteries (CA), is the main method of treatment preventing the development of cardiovascular complications during and after the treatment of oncopathology. Currently, there are many studies described in foreign literature that have assessed the results of single-stage surgery in this category of patients - coronary artery bypass grafting (CABG) and surgical treatment of oncopathology. A two-stage approach is also used as an alternative to single-stage intervention. In connection with the spread of endovascular myocardial revascularization methods, the assessment of staged surgical treatment of patients who underwent coronary artery stenting before the start of oncopathology treatment is of great interest. However, at present, few studies have been conducted that have assessed the effectiveness of primary percutaneous coronary intervention (PCI) in patients with oncopathology, and the data obtained are quite contradictory. A number of studies have assessed only the immediate results of two-stage treatment performed in patients with coronary artery disease and oncopathology. It should be taken into account that there have not yet been studies in this area on a sufficiently large number of patients to determine clear criteria by which it would be necessary to recommend performing angioplasty with stenting as the first stage in patients with coronary heart disease and oncopathology. Nevertheless, a number of studies have shown high efficiency of primary myocardial revascularization in this category of patients.